Identifying The Association Between Inflammatory Markers And Cycle Threshold Of RT-PCR In Paediatric COVID-19 Infection (Journal of Pharmaceutical Negative Results, 2022)
Background: Pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses a significant threat tohealthcare and is classified as a global pandemic. This study aims to find the association between the inflammatory marker CRP, LDH,Ferritin, D-dimer, and the cycle threshold of SARS CoV2 in the pediatric populationMethods: Patients admitted with COVID-19 infection (SARS CoV2 Real-Time PCR positive) from November 2020 to October 2021,were included in this study. The cycle threshold (Ct) of SARS CoV2 Real time-PCR test, serum lactate dehydrogenase (LDH), Creactive protein (CRP), serum Ferritin, D-dimer, white cell counts including absolute neutrophil and absolute lymphocyte count wereanalysed in these patients. Patients were divided into two groups based on the Ct (cycle threshold) value of SARS CoV2 RT-PCR forstatistical analysis (Ct<=26 and Ct>26). Statistical analysis using the area under the curve with a Z score (95% confidence interval)was used to detect the significance between the serum parameters and the cycle threshold of RT-PCR in COVID-19 infection. Patientswere grouped into asymptomatic, mild, moderate, and severe COVID-19 based on their clinical presentation. Unpaired t-test was usedto identify a statistically significant correlation between clinical presentation and the serological parametersResults: Out of 1125 suspected COVID-19 patients, 47 patients (4% positivity) were identified as COVID-19 positive using RT-PCR.The mean age group of males was 8.74±5.11 years and females was 9.45±5.87 years. 2% of patients had severe and 13% of patientshad moderate COVID-19 clinical presentation. The area under the curve analysis using a Z score with 95% CI identified a statisticallysignificant correlation between the cycle threshold of SARS CoV2 RT -PCR and absolute lymphocyte count (p-value 0.04). Nostatistically significant correlation was identified between D-dimer, serum LDH, serum ferritin, total white cell count, and the cyclethreshold of SARS CoV2 RT-PCR. Unpaired t-test showed a statistically significant correlation between clinical presentation and LDH,CRP, and D-dimer.Conclusion: The cycle threshold of RT-PCR does not show an association with serological parameters such as CRP, LDH, D-dimer,and serum ferritin. Absolute lymphocyte count can be used as an indicator to identify patients with low Ct values in SARS CoV2 RTPCR.